The Role of Village Assistants in the Village Program Sustainable Development Goals - Jamaluddin, Jamaluddin; Umar, Umar; Mukhlis, Suardi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Village assistants are a team within an organization where village assistants coordinate with volunteers formed to implement the SDGs program. This research used qualitative descriptive research methods to determine the role of village assistants in the village Sustainable Development Goals (SDGs) program in Sanjai village, East Sinjai sub-district. This research data consisted of primary data and secondary data obtained using interview, observation, and documentation techniques. The results of this research show that the village assistants' role in carrying out the Village SDGs program is as a volunteer sub-district coordinator who is tasked with monitoring all volunteers and teams who participate in helping run the Village SDGs (Sustainable Development Goals) program. As is known in the indicators regarding Village Facilitators as follows: Assistance in planning it can be seen that the SDGs program is very important where the assistant provides direction and motivation that influences the village government to achieve the SDGs program goals related to SDGs Villages without poverty in Sanjai Village and The planning that is carried out is that the assistant prepares a prospective team of volunteers who will carry out data collection on the poor by showing the Village Assistance Decree number 10 of 2021 concerning the formation of volunteers to update SDGs data in Sanjai Village in 2021. The role of the village assistant in the Village SDGs program in Sanjai Village is to provide assistance where the assistance referred to planning, implementation, and monitoring of the program being run, apart from that the village assistant also carries out organizing to make it easier to divide volunteer team groups into divisions of work activities that each volunteer team will carry out before carrying out SDGs data collection where The data collection in question is very focused on collecting data on Village SDGs without poverty, which is the main goal that is very global.